carbonate scale formation and control - MacAdam, Jitka (Cranfield University, 2005)
Scale formation in domestic appliances is a widespread problem in the UK. This project has focussed on calcium carbonate scale formation in electric showers. A literature survey identified that CaCO; deposition on heated surfaces could be controlled by chemical or non chemical methods, each with various degrees of effectiveness. One of the most effective control methods was the addition of chemicals, although this may not be the most suitable option for the domestic environment. So here the chemical inhibitors tested were used for a benchmark for all the other studies. Two laboratory tests were involved t allow u to study CaCO; precipitation and scale formation. The effect of chemical additives on CaCO; precipitation was investigated using a jar tester. The longest delay to precipitation was obtained by polyacrylic acid dosing, closely followed by zinc. To study CaCO; formation on a heated surface, a rapid scaling test was developed. This test was conducted at 42°C and 70°C to examine and compare a range of treatment options, including chemical dosing, electrolytic, magnetic and electronic water conditioning and low fouling surfaces. From the options examined, the most successful was electrolytic dosing of zinc/copper media with over 95% reduction in scaling at both temperatures. Further, the use of low fouling surfaces, such as Diamond - like carbon coating could also potentially be used in electric showers. Reduction in scaling achieved on this surface was on average 68%. Surface properties of the materials were analysed using an atomic force microscope and their relationship with the scaling behaviour of the surfaces examined. The scaling rates at both temperatures typically increased with increasing adhesion force but no clear relationship was found between the roughness of the surfaces and their scaling behaviour. The relationship between CaCO3 precipitation and scale formation in synthetic solution and natural hard water was also explored here. The induction period in natural hard water was 55 minutes longer and the scaling rate 40% lower than i synthetic hard solution of similar composition. In addition, two shower test rigs, one based at Cranfield University and the other in Attleborough were used in this study. These were used primarily to enable the compilation of background data on scale formation in electric showers, where it was found that the design of the unit has a significant influence on the scale formation. The test rig was also used t test the strategies identified during the laboratory phase of the work. It was found that electrolytic zinc dosing reduced scaling by up to 54%, depending on the shower unit design.